When distance enhances closeness: How Vietnamese international students and their back-home parents experience their long-distance relationships - Bui, My Le Hoang; Russell, Laura D. (Journal of International Students, 2024)
Exploring international students’ long-distance relationships with their back-home families is important for understanding how to support their stability and growth. Using qualitative interviews and surveys, this research explored perspectives from both international students and their parents about their remote interactions while oceans apart. Findings indicate three transformative shifts that enhanced the quality of student-parent relationships through their distance: a) incidental to intentionally motivated interactions, b) task-oriented to person-centered attention, and c) authoritarian to communally-oriented dispositions. These shifts fostered a greater sense of trust, support, and intimacy between international students and their back-home parents. Interweaving Construal Level Theory with the findings, this study offers implications for informing international students and their parents on developing effective, long-distance relationships.